Chromosome-level genome assembly of the largefin longbarbel catfish (Hemibagrus macropterus) - Ye, Huan; Fan, Jiahui; Hou, Yanling; Yue, Huamei; Ruan, Rui; Li, Shuang; Hu, Chongjiang; Xie, Yong; Li, Chuangju (Frontiers in Genetics, 2023)
The largefin longbarbel catfish, Hemibagrus macropterus, is an economically important fish species in southwestern China, with males growing faster than females. This study presents a high-quality chromosome-level genome assembly of the largefin longbarbel catfish, generated by integrating Illumina short reads, PacBio HiFi long reads, and Hi-C data. The assembled genome size was 858.5 Mb, with a contig and scaffold N50 of 5.8 Mb and 28.4 Mb, respectively. A total of 656 contigs were successfully anchored to 30 pseudochromosomes with a BUSCO score of 97.7%, consistent with the number of chromosomes analyzed by karyotype. The genome contained 29.5% repeat sequences, and a predicted total of 26,613 protein-coding genes, of which 25,769 (96.8%) were functionally annotated in different databases. Evolutionary analysis showed that H. macropterus was most closely related to H. wyckioides, with a divergence time of approximately 16.3 million years. Chromosomal syntenic relationships among H. macropterus, H. wyckioides, and Pelteobagrus fulvidraco revealed a one-to-one relationship for most chromosomes, except for break, fission, and inversion of some chromosomes. The first high-quality reference genome will not only provide a valuable genetic resource for the study of sex determination mechanisms and genetic breeding of largefin longbarbel catfish, but also contribute to comparative analyses of genome and chromosome evolution within Siluriformes.